ANALISIS EFEKTIFITAS KEBIJAKAN PAJAK, LINGKUNGAN WAJIB PAJAK DAN KESADARAN WAJIB PAJAK TERHADAP KEGIATAN TRANSAKSI E-COMMERCE - Alfredo Rachman, Ngadiman (Fakultas Ekonomi, Universitas Tarumanagara, 2020)
The purpose of this study is to find out the effectiveness of Indonesian tax policy on E-Commerce transactions and their impact on the environment of taxpayers and taxpayer awareness of E-Commerce transactions for the 2019 period. Samples using the purposive sampling method included in the non- probability sampling where 107 samples have been collected. The data processing technique uses the help of the Statistical Package for the Social Sciences 25 program (SPSS 25.0) and Microsoft Excel 2019. The results of this study partially show that tax policy has a significant influence on E-Commerce transaction activities, while the taxpayer environment and compulsory awareness tax does not have a significant effect on E-Commerce transaction activities. But simultaneously, this study shows that tax policy, the taxpayer environment and taxpayer awareness have a significant influence on E-Commerce transaction activities.